2012
DOI: 10.1103/physreve.86.061108
|View full text |Cite
|
Sign up to set email alerts
|

Quantum heat engine in the relativistic limit: The case of a Dirac particle

Abstract: We studied the efficiency of two different schemes for a quantum heat engine, by considering a single Dirac particle trapped in an infinite one-dimensional potential well as the "working substance." The first scheme is a cycle, composed of two adiabatic and two isoenergetic reversible trajectories in configuration space. The trajectories are driven by a quasistatic deformation of the potential well due to an external applied force. The second scheme is a variant of the former, where isoenergetic trajectories a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 23 publications
8
78
0
3
Order By: Relevance
“…The first law of quantum thermodynamics is fully addressed in many works [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and gives us the possibility to explore different quantum cycles and compare them with the classical analogues. To derivate this law simply, consider a Hamiltonian with an explicit dependence of some parameter that we will call µ in a generic form [25].…”
Section: The First Law Of Quantum Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first law of quantum thermodynamics is fully addressed in many works [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and gives us the possibility to explore different quantum cycles and compare them with the classical analogues. To derivate this law simply, consider a Hamiltonian with an explicit dependence of some parameter that we will call µ in a generic form [25].…”
Section: The First Law Of Quantum Thermodynamicsmentioning
confidence: 99%
“…The possibility to create an alternative and efficient nanoscale device, like its macroscopic counterpart, introduces the concept of the quantum engine, which was proposed by Scovil and Schultz-Dubois in the 1950's [1]. The key point here is the quantum nature of the working substance and of course the quantum versions of the laws of thermodynamics [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The combination of these two simple facts leads to very interesting studies of well-known macroscopic engines of thermodynamics, such as Carnot, Stirling and Otto, among others [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The last equation corresponds to the microscopic formulation of the first law of thermodynamics [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][25][26][27]31,34,35]. The first term in Equation (10) is associated with the energy exchange, while the second term represents the work done.…”
Section: Thermodynamics and Magnetic Enginementioning
confidence: 99%
“…It is important to highlight the work of Zheng and Poletti [36], where they derived a general form for the efficiency of quantum Otto cycles with power law trapping potentials, corresponding to Equation (11), and showed that γ must be equal to three. We remark that this result requires that two conditions are met.…”
Section: Magnetic Enginementioning
confidence: 99%
See 1 more Smart Citation